Strategi Pengembangan Kampung Atas Air Berbasis Ekowisata di Kelurahan Margasari, Kota Balikpapan - Asri Prasaningtyas; Rifky Safwan R; Renisah Nur; M. Umar Ibrahim (COMPACT: Spatial Development Journal, 2023)
Ecotourism is one of the effort in region development through the tourism sector, in addition to emphasize the function of natural tourism resources that are environmentally sound, ecotourism also contributes to environmental conservation and the community as the main player of its development. Kampung Atas Air Margasari is a village that has a variety of potential coastal resources, thus it supports the idea of the village is designated as a tourism area. However, Kampung Atas Air Margasari still has several problems such as the lack of supporting facilities and infrastructure and also the lack of community involvement in the development of tourist sites. Therefore it is necessary to conduct a study to analyze the potential and problems of ecotourism development in Kampung Atas Air Margasari. To achieve this goal, it is done by analyzing the components of tourism related to existing conditions such as Strengths, Weaknesses, Opportunities, and Challenges. After that, a strategy for developing existing ecotourism areas will be carried out by focusing on two targets, the first one is to evaluate the suitability of the ecotourism theory with the existing conditions of ecotourism in Kampung Atas Air Margasari, and the second one is to formulate an ecotourism development strategy in Kampung Atas Air Margasari by conducting a SWOT analysis and a descriptive analysis.